Element differentiation with a Hartmann- based X-ray phase imaging system. Issue 5 (3rd September 2022) - de La Rochefoucauld, Ombeline; Begani Provinciali, Ginevra; Cedola, Alessia; Cook, Philip K.; Di Lillo, Francesca; Dovillaire, Guillaume; Harms, Fabrice; Idir, Mourad; Levecq, Xavier; Oudjedi, Laura; Phan, Tan-Binh; Piponnier, Martin; et al.
ABSTRACT: Significant efforts are currently ongoing in X-ray imaging to provide multimodal imaging systems, targeting better sensitivity and specificity for both biomedical or non-destructive testing applications. Knowing the elemental composition of specific structures, such as breast microcalcifications in mammography, would help to differentiate malign and benign tumours. Standard X-ray Phase Contrast Imaging techniques provide only qualitative information on elements with similar absorption properties. However, their chemical composition can be determined from the measurement of the phase as it is directly related to the optical index of elemental materials. We will show new experimental results obtained with an X-ray phase imaging system based on a Hartmann mask. Early data treatment succeeded in retrieving both the real and imaginary parts of the refractive index. The system demonstrates the capability to discriminate materials based on elemental composition.